2021
DOI: 10.1590/1678-9199-jvatitd-2020-0155
|View full text |Cite
|
Sign up to set email alerts
|

Vector saliva controlled inflammatory response of the host may represent the Achilles heel during pathogen transmission

Abstract: Infection with vector-borne pathogens starts with the inoculation of these pathogens during blood feeding. In endemic regions, the population is regularly bitten by naive vectors, implicating a permanent stimulation of the immune system by the vector saliva itself (pre-immune context). Comparatively, the number of bites received by exposed individuals from non-infected vectors is much higher than the bites from infected ones. Therefore, vector saliva and the immunological response in the skin may play an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 161 publications
(190 reference statements)
0
3
0
1
Order By: Relevance
“…Arthropod vector immunity is poorly understood, including the role that the arthropod immune system has on microbevector interactions and its effects on arthropod populations in nature [29]. Saliva-assisted transmission (SAT) of vector pathogens is an important but poorly understood mechanism in vector-borne disease [30][31][32]. Salivary ChE injected into host tissue during blood feeding of vector arthropods is hypothesized to alter the cholinergic balance and control of developing immune responses of the host in response to tissue damage and the presence of pathogens or foreign antigens [11].…”
Section: Discussionmentioning
confidence: 99%
“…Arthropod vector immunity is poorly understood, including the role that the arthropod immune system has on microbevector interactions and its effects on arthropod populations in nature [29]. Saliva-assisted transmission (SAT) of vector pathogens is an important but poorly understood mechanism in vector-borne disease [30][31][32]. Salivary ChE injected into host tissue during blood feeding of vector arthropods is hypothesized to alter the cholinergic balance and control of developing immune responses of the host in response to tissue damage and the presence of pathogens or foreign antigens [11].…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be seen if these vaccines will differ significantly in side effect profile. The importance of continued research with full genome vaccines has been emphasized, 11 and recent studies have identified possible vaccine targets in mosquito saliva that may influence infection rates 51 . Research on both is ongoing.…”
Section: Diagnosis Treatment and Preventionmentioning
confidence: 99%
“…Additionally, mosquito saliva contains molecules that could alert the immune system of the host which potentially may block viral transmission, therefore, mosquito saliva components are being studied as promising candidates for vaccine development 21 . Mosquito saliva has recently also been shown to contain bacteria 22 .…”
Section: Introductionmentioning
confidence: 99%